Effect of drip irrigation levels and fertigation on capsicum cultivars under protected cultivation (Indian Journal of Arid Horticulture, 2016)
An experiment was conducted during 2010-11 and 2011-12 in poly-house at Niche Area Excellence Farm, Bikanerto study the effect of drip irrigation and fertigation levels on plant height, fruit yield, and water use efficiency of capsicum.The treatments consists of three drip irrigation schedules viz. 40, 60 and 80% ETc and three fertigation levels viz. 75%, 100%and 125% of recommended dose of fertilizers. The experiment was conducted in randomized block design and replicatedthrice. The study indicated that there was increase in plant height, fruits /plant and fruit yield with increase in irrigation levelsfrom 40% to 80% ETc. but the water use efficiency decreases with increasing irrigation levels. The study further indicatedthat plant height, fruits /plant, fruit yield and water use efficiency also increased with increasing the fertigation levels from75% to 125% recommended dose of fertilizer.
Keywords: Fertigation; drip irrigation level; capsicum; water use efficiency